The Greeks in Australia - Tamis, A. M. (Anastasios M.); Cambridge eBooks (Cambridge : Cambridge University Press, 2005)
The Greeks have made an enormous contribution to Australian cultural and social life, and this book vividly tells their story. Beginning with an examination of the conditions in Europe that led to migration, it details the role of the Greeks in Australian settlement, the two large waves of Greek migration in the nineteenth and twentieth centuries, and the ways in which the Greeks have maintained a solid sense of Greek cultural expression. Numbering approximately half a million, the Greek community in Australia comprises the second largest ethnic minority after the Italians. The contribution of Greek settlers to the large industrial cities and other major urban centres modernised them by injecting new ideas into the economic, social and political life of their new environment. The role of Greek settlers has been vital in building the nation we have today.
Hellas of diaspora -- The Greeks discover Australia -- Demographic characteristics -- Social and community life -- The years of respectability -- The culture and civilisation -- From migrants to citizens.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Greeks -- Australia -- Social life and customs; Greeks -- Australia -- History; Immigrants -- Australia -- History; National characteristics, Australian; Australia -- Emigration and immigration -- Social aspects; Greece -- Emigration and immigration -- Social aspects; Australia -- Ethnic relations; Electronic books